2004
DOI: 10.1111/j.1541-1338.2004.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Setting Agendas and Designing Alternatives: Policymaking and the Strategic Role of Meetings1

Abstract: This paper investigates the role of strategic forums-such as special commissions, task forces, roundtables, working groups, summits-in the policy process. Reviewing prominent theories about policymaking, the author suggests ways in which strategic forums might fit within these frameworks as an analytically distinct policy lever. The paper examines existing literature on such forums, and identifies characteristics of "meetings that matter"-those gatherings that appear to have achieved some policy traction in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…One such strategy concerns policy‐sector differences. Tepper (2004) found that input from gatherings such as summits and meetings of experts influenced policy‐making more in some sectors than in others, and Askim (2007) found the same for input from performance evaluations. Hence, future research should ask if citizen input influences policy outcomes more in some policy sectors than in others.…”
Section: Discussionmentioning
confidence: 92%
“…One such strategy concerns policy‐sector differences. Tepper (2004) found that input from gatherings such as summits and meetings of experts influenced policy‐making more in some sectors than in others, and Askim (2007) found the same for input from performance evaluations. Hence, future research should ask if citizen input influences policy outcomes more in some policy sectors than in others.…”
Section: Discussionmentioning
confidence: 92%
“…Much of this research comes from political studies, analysing the role of meetings in the public policy-making process. Meetings are important for setting agendas (Adams 2004;Tepper 2004), building commitment (Terry 2001) and providing information to policy makers (Adams 2004) rather than for generating policy decisions as such. Other anthropological and sociological research focuses upon variations in the form and function of meetings in different societies (e.g.…”
Section: Research On Meetingsmentioning
confidence: 99%
“…this merit is meaningful in resolving conflicts of interest, because frequent face-to-face contact reduces conflicts by facilitating the resolution of misunderstandings between unconnected groups (cook, 1984;forbes, 1997;harrington & Miller, 1992;Jackson, 1993;Nelson, 1989;Patchen, 1999;Pettigrew, 1998;Williams, 1970) and promotes intergroup trust and decreases transaction costs between groups (Doney & cannon, 1997;Nicholson, compeau, & Sethi, 2001;Williamson, 1981). that is to say, public meetings inexpensively help policy stakeholders to understand one other (Mccomas, 2003;Mccomas et al, 2006) and enhance networking between groups (Adams, 2004;checkoway, 1981;tepper, 2004).…”
Section: Public Meetings As Open Low-cost Interaction Venuesmentioning
confidence: 99%
“…Moreover, many studies maintain that public meetings have positively affected stakeholder conflict resolution. Public meetings provide an accessible venue for policy stakeholders to communicate with one another and discuss their policy goals (Adams, 2004;Mccomas, 2001;Sinclair, 1977); they sustain robust policy communities and avoid the unintended consequences of making and implementing policy (Mccomas, besley, & black, 2010;tepper, 2004); and they increase policy stakeholders' acceptance of policy outcomes by promoting procedural justice in policy-making processes (Mccomas et al, 2010).…”
mentioning
confidence: 99%